The Influence Of Competence, Motivation, And Work Discipline On Employee Performance At The Mojokerto Branch Of Perum Bulog - Devi Dwi Anggraeni; Budi Prabowo (International Journal of Social, Economic, and Business, 2025)
This research examined the relationships between three independent variables—employee competence (X1), employee motivation (X2), and work discipline (X3)—and their impact on employee performance (Y) at the Mojokerto Branch Office of Perum Bulog. The research design employed an associative quantitative approach to analyze variable correlations. Using probability sampling methods, 34 employees were selected from the total workforce at the Mojokerto Branch. Data analysis was performed using multiple linear regression techniques through SPSS version 27. The statistical analysis yielded several key findings. The combined effect of all three independent variables demonstrated significant influence on employee performance, with a statistical value of 4.949. Individual variable analysis revealed that employee competence (X1) significantly impacted performance (value: 2.368), while employee motivation (X2) showed no significant effect (value: 0.937). Work discipline (X3) emerged as a strong individual predictor of employee performance, yielding a statistical value of 2.670. All analyses were conducted using SPSS 27 to ensure statistical validity and reliability.